The Role of Peer Tutoring in Improving the Quality and Efficiency of Final Assignment Completion for Working Students - Budiati , Eryana Fatimasari Retno (LP2M IAIN Sultan Amai Gorontalo, 2026)
This action research aims to identify and optimize the role of peer tutoring as a flexible mentoring system in assisting students of the Special Education (PLB) Study Program, Faculty of Social and Political Sciences, Universitas Negeri Semarang (UNESA), especially working students, in completing their Final Projects (TA) effectively and efficiently. The study used an action research approach involving two students who experienced delays in completing their TA (PT and PP) and two graduate students as peer tutors. The research instruments included a peer tutoring guide booklet that had been validated by material and design experts, a pretest–posttest instrument to measure the increase in understanding of TA preparation, and an assessment sheet for the effectiveness of the program by students and supervisors. The results showed that the peer tutoring guide booklet was declared very feasible (average score of 4), there was a significant increase in understanding from pretest to posttest by 29.41% in the PT subject and 52.94% in the PP subject, as well as an increase in the completeness of the TA proposal components, namely the PP subject from 15 to 24 components and the PT subject from 17 to 22 components. Furthermore, student assessments of the program's effectiveness indicated a strong agreement with an average score of 4.4–4.8, particularly regarding the flexibility of mentoring and increased learning motivation. Thus, the peer tutoring model has proven highly effective as a flexible mentoring system that can improve academic quality, time efficiency, and student learning independence in completing their final assignments.